If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0=(-6)+a/3
We move all terms to the left:
0-((-6)+a/3)=0
We add all the numbers together, and all the variables
-((-6)+a/3)=0
We multiply all the terms by the denominator
-((-6)+a=0
| 2t2-5t+3=0 | | -25r^2-10r+1=0 | | X+679/x=104 | | 5x-10+60=360 | | 5(x+2)=3x+11 | | 9a+28=4a+39a+28=4a+3 | | 65.94=3.14r^27/3 | | -10+4x-x=5 | | 75=4a-17 | | 10+2x+7x=91 | | 80x-8=80 | | 1=8x=22=x | | 0.09p-0.04=0.09p+0.06 | | 9x-3x+17=53 | | y-2/3+2y+1/6=y-y+4/8 | | 2x=25=9x-59 | | 3=5w-1 | | 49/56=12/f | | 1/6d-3/2=1/2d+5/6 | | (3^x+3)+(9^x+2)=4 | | x=11/15x+20 | | x+(.07)(x)=259 | | 2/3n-1/5=2/5n | | -11w+8=5w+168 | | 5/13=t-6/13 | | y=-4.5+15 | | -1/10x+4=8/5 | | 11z-304=6(4-52) | | 2x+9x=36 | | X2-14x+45=0 | | 8p+2=74 | | x-0.4=30 |